British Association of Urological Surgeons (BAUS) consensus document for the management of male genital emergencies – penile fracture. (2nd April 2018) - Rees, Rowland W.; Brown, Gareth; Dorkin, Trevor; Lucky, Marc; Pearcy, Richard; Shabbir, Majid; Shukla, Chitranjan J.; Summerton, Duncan J.; Muneer, Asif; ,
Abstract : Male genital emergencies relating to the penis and scrotum are rare and require prompt investigation and surgical intervention. Clinicians are often unfamiliar with the management of these conditions and may not work in a specialist centre with on‐site expertise in genitourethral surgery. The aim of these consensus statements is to provide best practice guidance for urological surgeons based in the UK which are developed by an expert consensus. Penile fracture is a rare emergency and in most cases requires prompt exploration and repair to prevent erectile dysfunction and penile curvature.